2009
DOI: 10.1001/archsurg.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hepatitis B Virus Infection in the Prognosis After Hepatectomy for Hepatocellular Carcinoma in Patients With Cirrhosis

Abstract: Infection with HBV is a strong predictive factor for lower RFS after hepatectomy for a single nodule of HCC of 5 cm or smaller in patients with cirrhosis, providing a further basis for adjuvant antiviral treatment. Patients who are seropositive for HBV with poorly differentiated HCC should also be considered to be at a high risk of recurrence and possibly included in a policy of salvage liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…With respect to small HCC ( 50 mm), Nathan et al 25 demonstrated that tumor size was still an important independent prognostic factor and that 20-to 50-mm tumors were associated with poorer prognosis compared with tumors smaller than 20 mm. 25 Similar results were also reported by Cescon et al, 23 who used a cutoff point of 30 mm. However, the use of the appropriate tumor size cutoff in patients with small HCC in predicting prognosis has been a matter of some debate.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…With respect to small HCC ( 50 mm), Nathan et al 25 demonstrated that tumor size was still an important independent prognostic factor and that 20-to 50-mm tumors were associated with poorer prognosis compared with tumors smaller than 20 mm. 25 Similar results were also reported by Cescon et al, 23 who used a cutoff point of 30 mm. However, the use of the appropriate tumor size cutoff in patients with small HCC in predicting prognosis has been a matter of some debate.…”
Section: Discussionsupporting
confidence: 79%
“…22,23 However, the prognosis of small HCC after surgery may vary even in patients with favorable tumor characteristics. We and others have confirmed that tumor size is an independent risk factor for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Distance from the resection margin, tumor multiplicity, the presence or absence of diabetes (12,16) and HBV DNA expression (17)(18)(19)(20) are also reported to be factors associated with NBNC HCC prognosis. Thus, the prognostic factors for NBNC HCC identified in the present study are similar to those for virus-related HCC (21,22).…”
Section: Discussionsupporting
confidence: 75%
“…Some studies of small HCCs have indicated that HBeAg positivity correlated with recurrence within 1 year, but not with long-term survival rates. 39,40 Similarly, in another study of HBV-DNA, an indicator of viral activity, it revealed that HBV-DNA was a major significant risk factor for delayed recurrence independent of tumor size, but did not significantly correlate with survival rates. 41 In our study, we analyzed the interaction of tumor size and HBeAg positivity.…”
Section: Discussionmentioning
confidence: 99%